Students’ Writing Research as a Tool for Learning – Insights into a Seminar with Research-Based Learning - Girgensohn, Katrin (Journal of Academic Writing, 2016)
Research-based learning is an approach that lets students conduct research to develop content knowledge. This article gives insights into a seminar that followed this approach. It was a collaboration between the writing center and the linguistics department at European University Viadrina in Germany with the aim to explore new ways of combining the learning of content knowledge and writing. In accordance with the stance of the Scholarship of Teaching and Learning (SOTL), this collaboration was meant to be a pilot to generate experiences and knowledge about this approach and its potential for combining discipline-specific learning and writing.